2019
DOI: 10.1590/s0004-2803.201900000-66
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia and Severity of Non-Alcoholic Fatty Liver Disease

Abstract: BACKGROUND: Non-alcoholic fatty liver disease is characterized by deposition of lipids in the hepatic parenchyma exceeding 5% of liver weight in the absence of other conditions, such as viral or alcoholic hepatitis and metabolic disease. Non-alcoholic fatty liver disease is the most common form of chronic liver disease in several countries. In addition to liver complications, recent studies have shown a relation between liver fat and sarcopenia. OBJECTIVE: Determine the association between sarcopenia and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In a population of 6451 patients with CVD, Srikanthan et al demonstrated that both disease-specific and all-cause mortality were significantly greater in those with lower compared to higher muscle mass, regardless of fat mass, indicating high muscle mass may play a protective role in CVD [199]. Sarcopenia is also independently associated with non-alcoholic fatty liver disease (NAFLD) and T2DM, both of which are risk factors for CVD [200,201]. A recent systematic review reported that gait speed and handgrip strength, both of which are used in some definitions of sarcopenia [1] and are dependent on muscle function, are associated with CVD mortality and in many of the included studies, this association was independent of traditional risk factors such as smoking and dyslipidemia [202].…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…In a population of 6451 patients with CVD, Srikanthan et al demonstrated that both disease-specific and all-cause mortality were significantly greater in those with lower compared to higher muscle mass, regardless of fat mass, indicating high muscle mass may play a protective role in CVD [199]. Sarcopenia is also independently associated with non-alcoholic fatty liver disease (NAFLD) and T2DM, both of which are risk factors for CVD [200,201]. A recent systematic review reported that gait speed and handgrip strength, both of which are used in some definitions of sarcopenia [1] and are dependent on muscle function, are associated with CVD mortality and in many of the included studies, this association was independent of traditional risk factors such as smoking and dyslipidemia [202].…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…Studies have also examined the relationship between NAFLD patients’ muscle strength and physical performance assessment. Cross-sectional studies have detected an association between lower muscle strength, NAFLD and liver fibrosis severity [ 37 , 62 , 63 , 64 , 65 , 66 ], and the association between SMM and NAFLD has also been investigated in children and adolescents. In a case–control study including 53 paediatric patients with NAFLD and 73 controls aged 9–15 years, the skeletal muscle-to-body fat ratio, assessed by BIA, was significantly lower in individuals with NAFLD than in those without (0.83 vs. 1.04, p = 0.005), even after adjusting for age, sex, BMI and serum glucose [ 67 ].…”
Section: Sarcopeniamentioning
confidence: 99%
“…SARC-F, the most-used tool to screen for sarcopenia risk, has low sensitivity and positive predictive value in patients with CLD [ 153 ], but when combined with HGS and the calf circumference or finger-circle test (i.e., the determination of whether or not the maximum non-dominant calf circumference is bigger than the individual’s finger-ring circumference, which is formed by the thumb and forefinger of both hands) it is a valuable screening method for sarcopenia [ 153 ]. As regards the assessment of muscle strength, contrary to the CST, low HGS has been associated with NAFLD presence [ 37 , 63 , 64 , 65 , 66 ] and severity [ 37 , 63 , 64 ] and with the presence of advanced liver fibrosis [ 65 ]. Furthermore, low HGS predicts a poor clinical outcome [ 175 ] and mortality [ 161 , 176 ] in patients with LC.…”
Section: Sarcopeniamentioning
confidence: 99%